The Business of iPhone and iPad App Development Making and Marketing Apps That Succeed - Wooldridge, Dave.; Schneider, Michael; SpringerLink (Online service) (Berkeley, CA : Apress : Imprint: Apress, 2011)
The phenomenal success of the iPhone, iPad and the iPod touch has ushered in a (3z(Bgold rush(3y (Bfor developers, but with well over 300,000 apps in the highly competitive App Store, it has become increasingly difficult for new apps to stand out in the crowd. Achieving consumer awareness and sales longevity for your iOS app requires a lot of organization and some strategic planning. Updated and expanded for iOS 4, this bestselling book will show you how to incorporate marketing and business savvy into every aspect of the design and development process, giving your app the best possible chance of succeeding in the App Store. The Business of iPhone and iPad App Development was written by experienced developers with business backgrounds, taking you step-by-step through cost effective marketing techniques that have proven successful for professional iOS app creators$1 (Bperfect for independent developers on shoestring budgets. No prior business knowledge is required. This is the book you wish you had read before you launched your first app!s
Keywords: Computer science; Computer Science; Computer Science, general